Diet quality : an evidence-based approach, volume 1 - Hunter, Lan-Anh; Patel, Vinood B.; Preedy, Victor R. (Nutrition and Health, 2013)
Diet quality is a broad term that encapsulates both perceived and actual practices, personal preferences and cultural diversity. Measuring dietary quality can be problematic and includes investigating food types, the number or size of portions or their frequency. Diet quality may also be related to the type of food being ingested, snacking and other eating habits. Manufactured beverages and fast food may also be included as well as microbiological quality and attempts to improve single food items such as meats or vegetables. In this book, Diet Quality: An Evidence-Based Approach, Volume 1 all of the major facets of diet quality in relation to health outcomes are covered. This important new text includes methods for determining diet quality while adopting a holistic approach to impart information on the major areas of concern or knowledge. Chapters link in measurable indices of health such as obesity, pregnancy outcomes, cancer and cancer outcomes, and mortality. This book represents a diverse set of subject matters and seeks to fill a gap in the literature at a time when there is an increasing awareness that well being is associated with the qualitative nature of diets.  Contributors are authors of international and national standing and emerging fields of science are incorporated. Diet Quality: An Evidence-Based Approach, Volume 1 is a useful new text designed for nutritionists, dietitians, clinicians, epidemiologist, policy makers and health care professionals of various disciplines.